2022
DOI: 10.1186/s13019-022-01803-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexmedetomidine supplementation for thoracoscopic surgery: a meta-analysis of randomized controlled trials

Abstract: Introduction The efficacy of dexmedetomidine supplementation for thoracoscopic surgery remains controversial. We conduct a systematic review and meta-analysis to explore the impact of dexmedetomidine for thoracoscopic surgery. Methods We have searched PubMed, EMbase, Web of science, EBSCO, and Cochrane library databases through September 2020 for randomized controlled trials (RCTs) assessing the effect of dexmedetomidine supplementation on thoracos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Several studies have confirmed that the combination of dexmedetomidine and local anaesthetics can produce better analgesic and sedative effects, for example, Blaudszun et al 46 found that intraoperative dexmedetomidine significantly reduced postoperative pain without causing delayed awakening, reduced the dosage of postoperative analgesics and reduced the incidence of adverse effects such as nausea and vomiting. Song et al 47 conducted a study in thoracic surgery and found that dexmedetomidine supplementation during thoracoscopic surgery greatly improved analgesia in thoracoscopic surgery. Dexmedetomidine is an effective adjuvant for prolonging the peripheral nerve blocking effect of local anaesthetics, 48 which induces depolarisation of the presynaptic membrane of the noradrenergic pathway in the blueprint and down the spinal cord 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed that the combination of dexmedetomidine and local anaesthetics can produce better analgesic and sedative effects, for example, Blaudszun et al 46 found that intraoperative dexmedetomidine significantly reduced postoperative pain without causing delayed awakening, reduced the dosage of postoperative analgesics and reduced the incidence of adverse effects such as nausea and vomiting. Song et al 47 conducted a study in thoracic surgery and found that dexmedetomidine supplementation during thoracoscopic surgery greatly improved analgesia in thoracoscopic surgery. Dexmedetomidine is an effective adjuvant for prolonging the peripheral nerve blocking effect of local anaesthetics, 48 which induces depolarisation of the presynaptic membrane of the noradrenergic pathway in the blueprint and down the spinal cord 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The proper tube position was confirmed by auscultation and fiberoptic bronchoscopy. The ventilation settings during surgery were tidal volume ( 7-10 mL kg -1 (ideal body weight) ), a fraction of inspired oxygen (0.5-1.0), and end-tidal CO 2 partial pressure (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Following surgery, patients were admitted to the Intensive Care Unit (ICU).…”
Section: Methodsmentioning
confidence: 99%
“…Hamed et al showed that adding dexmedetomidine in ultrasound-guided ESPB is associated with a better analgesic effect by reducing intraoperative fentanyl and postoperative morphine consumption with a more prolonged analgesic effect and stable hemodynamics (39). Also, Song and Lu in a meta-analysis of randomized controlled trials reported that dexmedetomidine administered before anesthesia in thoracoscopic surgery can substantially improve the analgesic efficacy (40). The study in which dexmedetomidine and dexamethasone were compared in prevention of postoperative nausea and vomiting after laparoscopic cholecystectomy (the patients received either single dose of dexmedetomidine or dexamethasone before skin incision) demonstrated that the patients in dexmedetomidine group had lower severity of pain, higher sedation score, requested the first analgesic postoperatively later, and the amount of postoperative administrated tramadol was lower (41).…”
Section: Impact Of Dexmedetomidine and Dexamethasone On Postoperative...mentioning
confidence: 99%
“…Midazolam and propofol are commonly applied anesthetics in elderly patients during surgery. The combination of these two agents has a good anesthetic outcome, but it cannot effectively protect organ functions[ 4 , 5 ]. Dexmedetomidine is a highly selective α2 receptor agonist, which has a good effect in reducing the body's stress response and in stabilizing the patient's intraoperative hemodynamics.…”
Section: Introductionmentioning
confidence: 99%